2017
DOI: 10.1155/2017/6847532
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Abiotic Stress Resistance Analyses of a Catalase Gene fromIpomoea batatas(L.) Lam

Abstract: As an indicator of the antioxidant capability of plants, catalase can detoxify reactive oxygen species (ROS) generated by environmental stresses. Sweet potato is one of the top six most important crops in the world. However, its catalases remain largely unknown. In this study, a catalase encoding gene, IbCAT2 (accession number: KY615708), was identified and cloned from sweet potato cv. Xushu 18. It contained a 1479 nucleotides' open reading frame (ORF). S-R-L, Q-K-L, and a putative calmodulin binding domain we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…These genes have a major role in detoxification of ROS in the plant cell, which is extremely harmful as it causes lipid oxidation, DNA damage, and apoptosis. In agreement with our study, the role of protein detoxification has been documented in many plant species, i.e., Ipomoea batatas 18,88 , Ipomoea pes-caprae 89 , Arabidopsis thaliana 90 , Nicotiana tabacum 91 , Oryza sativa L. 92 and Solanum lycopersicum 93 . In addition, TSA genes are involved in the detoxification of reactive oxygen species (ROS), reactive sulfur species (RSS), and reactive nitrogen species (RNS).…”
Section: Discussionsupporting
confidence: 92%
“…These genes have a major role in detoxification of ROS in the plant cell, which is extremely harmful as it causes lipid oxidation, DNA damage, and apoptosis. In agreement with our study, the role of protein detoxification has been documented in many plant species, i.e., Ipomoea batatas 18,88 , Ipomoea pes-caprae 89 , Arabidopsis thaliana 90 , Nicotiana tabacum 91 , Oryza sativa L. 92 and Solanum lycopersicum 93 . In addition, TSA genes are involved in the detoxification of reactive oxygen species (ROS), reactive sulfur species (RSS), and reactive nitrogen species (RNS).…”
Section: Discussionsupporting
confidence: 92%
“…CAT gene expression is also affected by the stress condition, and it significantly increased after 2 days. A Similar result in Ipomea batatas was reported by literature [30] CAT gene expression is increased significantly after 2 days and decreased on the 20 days. The same finding is observed in other plants such as Pitaya [36], rice [37], Medicago falcet, and Cleome spinosa.…”
Section: Apx and Cat Gene Expressionsupporting
confidence: 91%
“…Stress affects the expression of the APX gene in the early stage of germination (11 days). After 6 weeks, it has no significant effect [29] [30]. In literature [31] was reported that some APX gene is increased under stress condition on rice.…”
Section: Apx and Cat Gene Expressionmentioning
confidence: 99%
“…And another one gene encoded homeobox domain containing protein ( LOC_Os11g06020.1 ), whose products are transcription factors sharing a characteristic protein fold structure that bound DNA [ 63 65 ], regulating gene transcription. Furthermore, another gene, LOC_Os11g44310.1 , which encoded calmodulin binding protein, regulated the expression of calmodulin to regulate the intracellular calcium concentration to control cells in many important biochemical reactions, which might play an important role in stress responses [ 66 ].…”
Section: Resultsmentioning
confidence: 99%